Surface Plasmon Resonance Alcohol Sensor with Ni(OH)2 Nanoflowers/Au Structure. (31st March 2023) - Sun, Meng; Wu, Haoyu; Song, Yutong; Wang, Qi
Highlights: Self-assembled the structure of Ni(OH)2 nanoflowers were synthesized. The sensitivity of the sensor was increased to 4127 nm/RIU and 232.4 nm/% after the self-assembled Ni(OH)2 nanoflowers were added behind the gold film to sensitize the sensor. The excellent sensing characteristics also indicate the potential application of the device in temperature monitoring and concentration detection. The performance test was carried out with the alcohol purchased from the store, and the result of the alcohol test was found to be consistent with reality. Abstract: Alcohol detection plays a key role in food safety and alcohol detection. Therefore, we propose a fast and label-free Ni(OH)2 nanoflowers/Au alcohol sensor based on surface plasmon resonance(SPR). Ni(OH)2 nanoflowers are grown on gold film by hydrothermal complex precipitation method. When the alcohol concentration increases, the resonance wavelength will be redshifted. More interestingly, the sensitivity of Ni(OH)2 nanoflowers/Au structure is increased to 232.4 nm/vol%. In the alcohol concentration range of 0 vol% − 60 vol%, the linearity between resonance wavelength and refractive index is greater than 0.98, which ensures the detection resolution and significantly improves the performance of SPR sensor. The high sensitivity and morphology advantage of nickel hydroxide indicate the potential of the device in alcohol detection.